Bilateral Luxatio Erecta – Etiology, Diagnosis and Management - Bawale, Rajesh; Soliman, Amr; Jain, Rohit; Singh, Bijayendra (Open Science Journal, 2021)
Luxation erecta is a rare form of shoulder dislocation, bilateral inferior shoulder dislocation is very rare and few cases have been published in the literature. We present a case of a male, fell down the ladder, presented with bilateral luxation erecta treated with close reduction, immobilisation and rehabilitation.